PENGARUH PERBEDAAN LEVEL FLOATING DOCK 10.000 TLC TERHADAP KONSTRUKSI WING WALL - Siti Arina Nur Aulia (2021)
Level differences on the floating dock that caused by uneven distribution loads along with the pressure of 17.990 DWT ships and the pressure of sea water on floating dock causing shear stress on wing wall construction. Shear stress analysis was necessary to determine the strength of construction. The analysis was done by checking the transverse bulkhead sections of middle-pontoons because it was the sections that has the biggest increase in loads and sticks to wing wall, that means if it has the biggest shear stress, it may affect the strength of wing wall structure construction as well. Therefore, those are the things that underpinned for writers to do the analysis with the aim of getting the value of shear stress with variations of condition, which is the increasing of sea water loads to the tune of 10-50% from initial load. Modelling and analysis process both were using SAP 2000, which is a software that based on finite element method. A material that used for floating dock is a standard steel material BKI ST-37 with certain criteria. Based on the result, maximum shear stress was obtained in 50% loads condition on section 2.b transverse bulkhead. It can be concluded that the value of shear stress has been exceeds the allowable shear stress limits from BKI 2019 regulation which is τ = 99,001 > τcr = 95 N/mm2 and it causing a cracking on wing wall construction.